Nastanek kondenzacijskih sledi za letali - Fifnja, Manca (Matrika, 2020)
The paper explains the theoretical background regarding contrails. The first part of the paper presents the history and theory of contrail formation, followed by a detailed presentation of the Schmidt-Appleman theory. The second part presents the impact of contrails on the atmosphere and reviews different conditions for contrail formation. The potential for contrail formation is presented, along with the coverage of contrails due to air traffic, the influence of flight elevation, and the influence of aircraft propulsive efficiency. The final part describes the balance between the influence of carbon dioxide emissions and the influence of contrails on the atmosphere.
Keywords: air traffic; atmosferska fizika; atmospheric physics; contrails; kondenzacijske sledi; letalski promet